Urban Households' Assessment of Environmental Safety: A Case Study of Ibadan, Nigeria - A.S. Oyekale; R.F. Ige (University of Sofia, 2012)
Safe environment is a prerequisite for healthy living and socio-economic development of any nation. In this study, we analyzed the different forms of environmental problems being faced by households in Nigeria's largest city. Data were collected from 120 households using the stratified sampling method. Our results show that majority of the households were faced with bushy and untidy environment, illegal structure/urban slum and improper disposal of refuse/feaces. Also, using the ranking method, the most pressing problems indicated to be solved are improper disposal of refuse and faeces, bad odors in the neighborhood, poor drainage and bushy/untidy environment. The study recommended serious enforcement of existing environmental laws in order to ensure safe environment for residents in Ibadan, among others.